Wavelets bases defined over tetrahedra - Boscardín, Liliana Beatriz (2006)
In this paper we define two wavelets bases over tetrahedra which are generated by a regular subdivision method. One of them is a basis based on vertices while the other one is a Haar-like basis that form an unconditional basis for Lp (T, Σ, μ), 1 < p < ∞, being μ the Lebesgue measure and Σ the σ - algebra of all tetrahedra generated from a tetrahedron T by the chosen subdivision method. In order to obtain more vanishing moments, the lifting scheme has been applied to both of them